THE COMPARISON OF ARRHYTHMOGENICITY OF DIFFERENT SURGICAL APPROACHES TO ATRIAL FIBRILLATION IN PATIENTS WITH CORONARY HEART DISEASE - A. M. Chernyavsky; Yu. E. Kareva; I. A. Pak; S. S. Rakhmonov; A. B. Romanov; E. A. Pokushalov (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To estimate the prevalence of iatrogenic atrial flutter in patients with coronary heart disease (CHD) and atrial fibrillation (AF) after two types of surgical operations: radiofrequency pulmonary veins isolation and radiofrequency modified mini Maze procedure; and to compare the results with control group of patients undergone aortic-coronary bypass grafting (CABG).Material and methods. Totally 95 patients included with CHD and persistent AF. Subjects were randomized into three groups: 1st (n=31) — with simultaneous CABG and radiofrequency ablation of pulmonary veins ostiums; 2nd (n=30) — simultaneous CABG and mini Maze procedure; 3rd control (n=34) — CABG only. For prolonged ECG monitoring the implanted devices Reveal XT were used in 53 subjects.Results. The patients escaped from left-atrial flutter were 90% in the 1st group. In the 2nd there was 1 case of left-atrial flutter (according to electrophysiological investigation — the leap through the mitral valve line), meaning 96,9% patients free from it. However there was no significant difference between 1st and 2nd groups (p=0,6). In the 3rd group postprocedure flutter developed in one case too, due to the scar on the left atrium wall after mitral valve regurgitation correction; so 97% patients escaped from flutter, but the difference was still not significant (p=0,4).Conclusion. In patients with CHD and AF it is recommended to perform radiofrequency modified mini Maze procedure combined with CABG due to its lower proarrhythmogenic effect. The rate of iatrogenic flutter is 3,1% after mini Maze and 10% after pulmonary veins ostiums isolation.